1994
DOI: 10.1210/endo.134.5.8156901
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glucagon-like peptide-1 secretion by muscarinic agonist in a murine intestinal endocrine cell line.

Abstract: Studies on the cholinergic regulation of intestinal L-cells have been focused on the release of enteroglucagon, but the signal transduction pathways were not defined. These were here investigated by using as index the release of immunoreactive glucagon-like peptide-1 (GLP-1) from the endocrine cell line STC-1, that has been shown to contain proglucagon mRNA transcripts. Abundant GLP-1 immunoreactivity was revealed in STC-1 cells at immunocytochemistry and by RIA. The cell content was 4927 +/- 689 pg/10(6) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The GLP-1 assay was performed as recently described (17,18). Briefly, antiserum against GLP-1-(7-36) amide was obtained in a rabbit by immunization with synthetic GLP-1-(7-36) amide conjugated to BSA and was used at a final dilution of 1:300,000.…”
Section: Riasmentioning
confidence: 99%
“…The GLP-1 assay was performed as recently described (17,18). Briefly, antiserum against GLP-1-(7-36) amide was obtained in a rabbit by immunization with synthetic GLP-1-(7-36) amide conjugated to BSA and was used at a final dilution of 1:300,000.…”
Section: Riasmentioning
confidence: 99%
“…An alternative model, the isolated canine L cell (25)(26)(27), provides a more homogeneous cell population, but this culture system requires centrifugal elutriation to prepare and is therefore relatively expensive. A secretin tumor cell line (STC-1) that secretes GLP-1 has also been used as an L cell model (28); however, STC-1 cells are poorly differentiated and multipotential. Hence, the similarity of this intestinal S cell model to the GLP-1-producing L cell is unclear.…”
Section: G Lucagon-like Peptide-1 (Glp-1) Is a Potent Stim-mentioning
confidence: 99%
“…Finally, as bethanechol acts through muscarinic receptors only, whereas carbachol binds to both muscarinic and nicotinic receptors, the present findings suggest a role for a muscarinic receptor in the regulation of GLP-1 secretion. Although the secretin tumor (STC-1) cell line is not a true model of the L cell, studies using these cells have indicated an involvement of the M3 receptor subtype in modulating GLP-1 release (28). Further investigations to determine the receptor subtype expressed by the GLUTag cells are therefore clearly warranted.…”
Section: Fig 1 Secretion Of Glp-1 By Glutag Cells In Response To Inmentioning
confidence: 99%
“…In this study, we show that TRPA1 channel is expressed in the human and mouse duodenum. In order to investigate the possible function we used mouse intestinal neuroendocrine cell line STC-1 as a well-established model for intestinal hormone release (CCK, GLP-1, GIP) [12][13][14][15] and show that activation of TRPA1 channels with mustard oil derived AITC elevates the intracellular Ca 2+ levels and stimulates cholecystokinin release.…”
Section: Introductionmentioning
confidence: 99%